Longitudinal relations between symptoms, neurocognition, and self-concept in schizophrenia - Hesse, Klaus; Kriston, Levente; Wittorf, Andreas; Herrlich, Jutta; Wölwer, Wolfgang; Klingberg, Stefan (Frontiers in Psychology, 2015)
Objective: Cognitive models suggest that the self-concept of persons with psychosis can be fundamentally affected. Self-concepts were found to be related to different symptom domains when measured concurrently. Longitudinal investigations to disentangle the possible causal associations are rare. Method: We examined a sample of 160 people with a diagnosis of schizophrenia who took part in a psychotherapy study. All participants had the DSM-IV diagnosis of a schizophrenia and pronounced negative symptoms. Neurocognition, symptoms and self-concepts were assessed at two time points twelve months apart. Structural equation modelling was used to test whether symptoms influence self-concepts (scar-model) or self-concepts affect symptoms (vulnerability model). Results: Negative symptoms correlated concurrently with self-concepts. Neurocognitive deficits are associated with more negative self-concepts twelve months later. Interpersonal self-concepts were found to be relevant for paranoia. Conclusion: The findings implicate that if deficits in neurocognition are present, fostering a positive self-concept should be an issue in therapy. Negative interpersonal self-concept indicates an increased risk for paranoid delusions in the course of one year. New aspects for cognitive models in schizophrenia and clinical implications are discussed